Calidad de servicio y satisfacción de los usuarios en los cajeros automáticos del Banco de la Nación, San Juan Bautista – 2023 - Yoplack Mori, Mauro Germán (2024)
The purpose of the present study was to identify the type of association that denotes the quality of service and user satisfaction of the ATMs of the National Bank headquarters San Juan in the province of Maynas, Loreto-Peru. The population is determined by all the users of this service of said agency, whose sample, when considered infinite and applying probabilistic sampling, resulted in 384 people. The applied research technique is the survey and its instrument is the questionnaire. The main hypothesis is that there is a positive and significant relationship between the variables under study. The hypothesis test was carried out with the Spearman coefficient with an alpha level of 0.05; The test result showed a value of Rho = 0.042 with a p-value of 0.410, so the research hypothesis is partially proven, in the sense that the relationship is positive, although of a very low intensity; more is not statistically significant, since the sig. of the test is greater than that of the investigation (0.410 > 0.05). At a descriptive level, with respect to the quality of the service, 87.50% perceive it as good and 4.17% as very good; while, with respect to user satisfaction, 57.81% say they feel satisfied and 25.26% very satisfied, both very positive results for the entity under study.